2014
DOI: 10.1038/srep05189
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of lactate dehydrogenase rescues mice from acidosis

Abstract: Acidosis causes millions of deaths each year and strategies for normalizing the blood pH in acidosis patients are greatly needed. The lactate dehydrogenase (LDH) pathway has great potential for treating acidosis due to its ability to convert protons and pyruvate into lactate and thereby raise blood pH, but has been challenging to develop into a therapy because there are no pharmaceutical-based approaches for engineering metabolic pathways in vivo. In this report we demonstrate that the metabolic flux of the LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…We showed that in the Group Ay/a-M600, the lactate level was doubled as compared to untreated agouti-mice. However, it was below the threshold of lactate concentration (10 mM), which in rodents characterizes the development of severe forms of lactic acidosis, leading to pathological changes [ 43 , 44 ] . We also showed the absence of the cumulative effect of MF, taken at a dose of 600 mg/kg, on the plasma levels of lactate, since there were no significant differences in the lactate concentration in agouti-mice treated with MF for one and ten days.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that in the Group Ay/a-M600, the lactate level was doubled as compared to untreated agouti-mice. However, it was below the threshold of lactate concentration (10 mM), which in rodents characterizes the development of severe forms of lactic acidosis, leading to pathological changes [ 43 , 44 ] . We also showed the absence of the cumulative effect of MF, taken at a dose of 600 mg/kg, on the plasma levels of lactate, since there were no significant differences in the lactate concentration in agouti-mice treated with MF for one and ten days.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the potassium level through enforced expression of potassium channels in T cells can enhance their antitumor activity (122). A lactate-binding compound has been recently developed as a potent pharmaceutical approach for engineering metabolic flux of lactate and normalizing the pH in vivo (245).…”
Section: Metabolic Optimization Of the Clinical Manufacture And Applimentioning
confidence: 99%
“…It also cannot reduce but can even exacerbate the lactate accumulation [ 1 ]. Furthermore, SB has several negative side effects, such as altering blood pressure and triggering apoptosis [ 12 ]. SB administration requires a functional cardio-respiratory system to exhale the extra CO 2 and there is a trend against using it in cardiac arrest patients.…”
Section: Current Non-ideal Therapeutic Agentsmentioning
confidence: 99%
“…Many other agents are being investigated to better manage LA. For example, the compound 5-amino-2-hydroxymethylphenyl boronic acid, a phenyl boronic acid derivative, binds lactate and normalizes the blood pH by increasing the consumption of protons via the LDH pathway [ 12 ]. Spermidine, with its activating effect on PDH phosphatase, can also activate PDH, stimulating the decarboxylation of pyruvate and inhibiting lactate accumulation [ 1 ].…”
Section: Current Non-ideal Therapeutic Agentsmentioning
confidence: 99%
See 1 more Smart Citation